Os espaços públicos e o direito à cidade - Mesquita, Rogério Garcia (2018)
This paper aims to diagnose the reasons for the fragmentation of modern cities, pointing to socio-spatial segregation as a consequence of the capitalist city model. Fear of violence and the search for security stem from segregation imposed, voluntary self-segregation and the decline of the public sphere of deliberation. Alternative models of social organization are presented, namely, Castoriadis' project of autonomy and democracy, Bookchin's libertarian municipalism and Harvey's dialectical utopianism, which mark institutional struggle and direct action to restore the public sphere, influence production of public spaces and to realize the right to the city.